Conditioned pain modulation (CPM) in children and adolescents: Effects of sex and age - Tsao, Jennie C. I. (2013)
Conditioned pain modulation (CPM) refers to the diminution of perceived pain intensity for a test stimulus following application of a conditioning stimulus to a remote area of the body, and is thought to reflect the descending inhibition of nociceptive signals. Studying CPM in children may inform interventions to enhance central pain inhibition within a developmental framework. We assessed CPM in 133 healthy children (mean age = 13 years; 52.6% girls) and tested the effects of sex and age. Participants were exposed to four trials of a pressure test stimulus before, during, and after the application of a cold water conditioning stimulus. CPM was documented by a reduction in pressure pain ratings during cold water administration. Older children (12–17 years) exhibited greater CPM than younger (8–11 years) children. No sex differences in CPM were found. Lower heart rate variability (HRV) at baseline and after pain induction was associated with less CPM controlling for child age. The findings of greater CPM in the older age cohort suggest a developmental improvement in central pain inhibitory mechanisms. The results highlight the need to examine developmental and contributory factors in central pain inhibitory mechanisms in children to guide effective, age appropriate, pain interventions.